AKTUALISASI DIRI SISWA SEBAGAI GENERASI Z DALAM PENGGUNAAN MEDIA SOSIAL TERHADAP PRESTASI BELAJAR - Huda, Muhammad Komarul; Aly, Hafizh Raihan; Sipayung, Miranda Irawan; Khodijah, Siti (Fakultas Keguruan Dan Ilmu Pendidikan, UM-Tapsel, 2024)
This literature study aims to determine the actualization of social media networks on academic learning achievements, especially for high school students or Generation Z and efforts to overcome dependence on social media networks. This type of research is qualitative research with a literature study method. The results of literature studies show that Generation Z students spend more time scrolling on social media. Social media that is often used by Generation Z students is Whatsapp, Instagram, Tiktok, Youtube, Facebook and Twitter. Today's Generation Z tends to get bored when they don't use social media because each social media has its own advantages and characteristics that make its users feel at home staring at their cellphone screens all day long. The intensity of social media use of Generation Z students averages more than 3 hours a day. Usually the electronic devices used to access social media include smartphones, laptops and other electronic devices. The positive impact of social media for Gen Z in using social media is to get information related to knowledge, tips and tricks related to learning and will make it easier when doing assignments so it is hoped that it will support each student's achievement. The surefire way for students to become Gen Z to overcome this dependency or addiction to social media, they do by managing or managing their time as well as possible, limiting the use of social networks, increasing outside activities so as to minimize opening social media, by turning off notifications so they can focus more on doing assignments or other things related to school or daily life.